Soft power jako narzędzie budowania „strategicznej głębi” w polityce zagranicznej Turcji w latach 2003–2016 - Fraszka, Łukasz Sławomir (Jednostka wobec globalnego wymiaru stosunków międzynarodowych, 2021)
The takeover of power in Turkey by the Justice and Progress Party in 2002 opened a new chapter for that country. The practical application of the doctrine of Ahmet Davutoğlu’s „strategic depth” and soft power resources has led to a redefinition of the state’s position in the international arena and a departure from the static foreign policy paradigm. This led to a change in the role and importance of Turkey as a participant in international relations and to its active involvement in global politics. This article attempts to answer a number of key questions relating to the issues in the title. First, it will answer what is the place and role of the soft power concept in international relations theory. Then, what role and significance did the doctrine of „strategic depth” play in Turkey’s foreign policy. Finally, how Turkey used the soft power concept in its foreign policy based on „strategic depth”. And what role did Ahmet Davutoğlu play in this. The historical method was used to achieve the research objective.